BELANJA DESA SEBAGAI DETERMINAN INDEKS PEMBANGUNAN MANUSIA PADA 21 KABUPATEN DI PROVINSI NUSA TENGGARA TIMUR - Putra Arismunandar Edon; M E Perseveranda; Henny A Manafe (Universitas Nusa Cendana, 2023)
The objective of this study is to analyze the influence of village expenditure on the Human Development Index in 21 districts in East Nusa Tenggara Province. This is secondary data obtained from the official website of the Statistics Center Bureau (BPS), which contains all reports of income realization and expenditures of the village government in 21 districts in East Nusa Tenggara Province from 2017 to 2020. The methods of analysis used in this study are descriptive analysis and panel data analysis. Results show that, simultaneously, village government expenditures, community development expenditures, and capital expenditures positively and significantly influence the human development index. Partially, village government expenditures negatively and significantly influence the Human Development Index. Community development expenditures and capital expenditures positively and significantly influence the Human Development Index. Keywords: Village Government Expenditures; Community Development Expenditures; Capital Expenditures; Human Development Index